Asymptotic analysis of drug dissolution in two layers having widely differing diffusivities. (31st January 2019) - Vynnycky, Michael; McKee, Sean; Meere, Martin; McCormick, Christopher; McGinty, Sean
Abstract: This paper is concerned with a diffusion-controlled moving boundary problem in drug dissolution, in which the moving front passes from one medium to another for which the diffusivity is many orders of magnitude smaller. The classical Neumann similarity solution holds while the front is passing through the first layer, but this breaks down in the second layer. Asymptotic methods are used to understand what is happening in the second layer. Although this necessitates numerical computation, one interesting outcome is that only one calculation is required, no matter what the diffusivity is for the second layer.